The citizen drone: protest, sousveillance and droneviewing. Issue 5 (19th October 2020) - Zuev, Dennis; Bratchford, Gary
Abstract : In this article we will discuss the use of drones, as well as the visual simulation of drone afforded aesthetics, by activists, artists and protesters. We use the existing literature of surveillance studies and visual studies to examine how exactly a drone-afforded visibility emerges and how it mediates the visibility of a particular community or space of contention. We draw on the concepts of "surveillance capacities" and (counter) visibility practices to analyse the process and production of drone (and drone-simulated) counter surveillant artist/activist visibility . The article makes several key points. The first one concerns the construction of protest space and the protest site volumetrically from the airborne perspective of the citizen drone via an assemblage of artist/activist practices. These practices include the use of drones, as well as drone-simulated imagery. The latter includes, DIY aerial camera rigs attached to kites and the use visual social media platforms such as Instagram to curate otherwise less visible military drone geographies more 'real' and proximate. The second concerns the visibility of subjects engaged in the protest space. And finally, we elaborate how events are presented dynamically (rhythmically) through drone videos and a drone-afforded visual grammar. Our assumption is that drones, as well as drone-simulated imagery allow the user to generate a hybrid participative (inclusive) visibility that makes protest more spectacular through its volumetric vision, subverting the visibility of control while striving for visibility of recognition. Overall, this article seeks to further elaborate on the visual turn within sociology, specifically in relation to what are now commonplace volumetric practices of power, representation and participation.